2021
DOI: 10.3390/polym13081187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitosan and Aloe Vera Extract Concentrations on the Physicochemical Properties of Chitosan Biofilms

Abstract: Chitosan films have been extensively studied as dressings in formulations for the treatment of chronic wounds. The incorporation of aloe vera (Aloe barbadensis Miller) into chitosan dressings could potentialize the healing process since aloe vera shows several pharmacological activities. This work aimed to evaluate the effect of aloe vera and chitosan concentrations on the physicochemical properties of the developed films. The films were obtained by casting technique and characterized with respect to their col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 40 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…Chitosan is a cationic polysaccharide produced through the deacetylation of chitin, a polysaccharide found in the exoskeleton of crustaceans. Antimicrobial activity, biocompatibility, and promotes wound healing, characteristics features that make it a suitable material for wound dressings [ 29 , 30 ].…”
Section: Films Containing Lipidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chitosan is a cationic polysaccharide produced through the deacetylation of chitin, a polysaccharide found in the exoskeleton of crustaceans. Antimicrobial activity, biocompatibility, and promotes wound healing, characteristics features that make it a suitable material for wound dressings [ 29 , 30 ].…”
Section: Films Containing Lipidsmentioning
confidence: 99%
“…The microstructure evaluation of emulsified chitosan films indicated that pure chitosan films presented a cohesive, dense structure, without the presence of pores or flaws [ 30 , 80 , 81 ]. When incorporating palmitic acid, the emulsified films presented a more amorphous matrix.…”
Section: Film Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The correct use of ointments and dressings influences the course of healing positively, and can reduce potential complications [ 1 ]. In this sense, some studies reporting the use of natural products have shown positive effects in the wound healing process, such as membranes based on, e.g., gelatin, chitosan, sodium alginate, and containing usnic acid [ 8 , 9 ], Vitis labrusca [ 10 ], aloe vera [ 11 ], Punica granatum Linn [ 12 ], and red propolis [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biopolymers materials, for example, are commonly used in the medical field as dressings, wound treatment, drug delivery, tissue engineering, and medical implants [ 4 , 5 ]. Chitosan is a natural cationic biopolymer [ 6 ] and has been considered in various biomedical applications, including wound healing, because of its many biological and physical-chemical attributes suitable for application in dressings [ 7 , 8 ]. Chitosan’s numerous essential advantages are related to its interaction with the tissue, causing no or low toxicity to degradation, as well as having anti-inflammatory and antibacterial effects [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%